2009
DOI: 10.21273/hortsci.44.3.666
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Climate on Fruit Development and Quality of Four Low-chill Peach Cultivars

Abstract: The effect of climate was observed on fruit quality of four low-chill peach cultivars (Flordaprince, Flordaglo, UFGold, and TropicBeauty). The cultivars were evaluated in three locations (north–central, central, and southwest Florida). Soluble solids content (SSC), titratable acidity (TA), SSC:TA ratio, fruit weight, blush, and fruit development period (FDP) were determined. Longer FDPs were observed at the north–central location than at the southwest location. Fruit development and the expression of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
1
17
1
2
Order By: Relevance
“…The trees were pruned in this way in order to be 2.8 m in height, as is done in commercial orchards in Florida. In other N studies, pruning was done only in the summer or was not reported . Pruning and fruit thinning decrease yield in peach trees, because of the removal of flower buds during winter pruning and the removal of fruit to obtain fruit of larger diameter .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The trees were pruned in this way in order to be 2.8 m in height, as is done in commercial orchards in Florida. In other N studies, pruning was done only in the summer or was not reported . Pruning and fruit thinning decrease yield in peach trees, because of the removal of flower buds during winter pruning and the removal of fruit to obtain fruit of larger diameter .…”
Section: Discussionmentioning
confidence: 99%
“…In other N studies, pruning was done only in the summer 10,20 or was not reported. 27,41,57,61 Pruning and fruit thinning decrease yield in peach trees, because of the removal of flower buds during winter pruning and the removal of fruit to obtain fruit of larger diameter. 58,59 Even though thinning decreases yield, the increase in fruit size improves marketability, which makes the practice cost-effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Zaragoza has a semi-arid climate with 17-mm average monthly rainfall during July and August (Agencia Estatal de Meteorología 2010). Weather in the form of precipitation and cloud cover may affect fruit quality if it occurs during the latter stages of fruit development (Wert et al 2009). In Republic of Korea, SSC reduction induced by heavy precipitation is a serious problem in quality aspects (Kwon et al 2008).…”
Section: Fruit Quality Traitsmentioning
confidence: 99%